Labor Quality Growth in Germany - Guido Schwerdt; Jarkko Turunen (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2009)
Extending the common baseline model in various dimensions does not fundamentally change the low contribution of labor quality to productivity growth in Germany. Labor quality growth is low owing to a small increase in the share of workers with higher education, a negative contribution from a higher share of females and declines in relative returns. The contribution of actual labor market experience is lower than suggested by an age proxy.
Keywords: E24; J24; O47; 330; Human capital; labour quality; productivity growth